Risk in sediment - impacted detention pond analysis using monte carlo simulation at Iskandar Malaysia (Nusajaya), Johor [electronic resource] - 209885 Irma Noorazurah Mohamad; Supiah Shamsudin, supervisor; Norhazilan Md. Noor, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2008